2022
DOI: 10.1111/jocn.16485
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue trajectory and its associated factors in patients after cardiac surgery: A longitudinal study

Abstract: Background: Fatigue is associated with multidimensional factors in heart failure patients. Investigating longitudinal changes in fatigue and its association in patients undergoing cardiac surgery is needed to create interventions for improving fatigue during recovery. Aims: This study examined the trajectory of fatigue and its associated factors over time in patients undergoing cardiac surgery.Methods: This longitudinal study enrolled 125 patients undergoing cardiac surgery in northern Taiwan. Patients complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
1
0
3
Order By: Relevance
“…Ünsal et al [24] indicated a strong correlation between the level of fatigue and sleep quality, also showing the influence of female gender on feeling a higher level of fatigue than men. Chou et al [33]. studied patients in the perioperative period undergoing cardiothoracic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Ünsal et al [24] indicated a strong correlation between the level of fatigue and sleep quality, also showing the influence of female gender on feeling a higher level of fatigue than men. Chou et al [33]. studied patients in the perioperative period undergoing cardiothoracic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Cerrahi girişim uygulanan hastalarda ameliyat öncesi anksiyetenin önemli belirleyicilerinden birisi olan yorgunluk kardiyak cerrahi hastalarının %73-82'sinde görülen ve ameliyat sonrası iyileşme sürecini olumsuz etkileyen önemli semptomlardan biridir. 8,[15][16][17] Bu çalışmada da bireylerin ameliyat öncesi dönemde orta düzeyde yorgunluk yaşadığı ve kadın, bekâr, sigara-alkol kullanan ve çalışan bireylerde yorgunluk düzeyinin istatistiksel olarak anlamlı düzeyde daha yüksek olduğu bulundu (p<0,05). Archana ve ark.nın çalışmasında da bireylerin çoğunluğunun ameliyat öncesi yorgunluk yaşadığı ve yorgunluk düzeyinin kadın ve çalışan bireylerde daha yüksek olduğu bulunmuştur.…”
Section: Bulgularunclassified
“…Gün içi r değeri 0,128 0,432 0,663 0,597 0,591 0,471 1 p değeri 0,170 0,000 0,000 0,000 0,000 0,000 anksiyete arasında pozitif yönde ilişki olduğu ve uyku kalitesi düşük olan bireylerde yorgunluk düzeyinin daha yüksek olduğu bildirilmektedir. 8,15 Bu çalışmadan elde edilen sonuçlar kardiyak cerrahi uygulanacak olan hastalarda yorgunluğun tanıtıcı özellikler, fizyolojik ve psikolojik boyutları içeren çok boyutlu bir semptom olduğu bilgisini desteklemektedir. 15 Bu nedenle kardiyak cerrahi uygulanacak hastalarda yorgunluk düzeyinin ve yorgunlukla ilişkili olan anksiyete ve uyku problemi gibi psikolojik ve fizyolojik sorunların, ameliyat öncesi erken dönemde belirlenmesi ve bireylerin yorgunluk düzeyini azaltacak hemşirelik girişimlerinin planlanmasının ameliyat sonrası dönemde hastaların iyileşmesine katkıda bulunacağı söylenebilir.…”
Section: Bulgularunclassified
See 1 more Smart Citation